Romantic relationship dysfunction in borderline personality disorder: a naturalistic approach to trustworthiness perception - Miano, Annemarie (Personality disorders, 2017)
Patients with borderline personality disorder (BPD) suffer greatly from their unstable interpersonal relationships. Studies on explanatory mechanisms driving social dysfunctions in patients’ real-life relationships are, however, lacking. Here, we aimed to investigate one of the most central aspects of close relationships, interpersonal trust, in romantic relationships of persons with BPD. We tested the hypothesis that patients with BPD show unstable trustworthiness perception toward their partner, which we expected to be most pronounced after a relationship-threatening situation. Thirty-one heterosexual couples in which the women were diagnosed with BPD and 36 healthy control (HC) couples (total N = 134) each discussed three different topics that where (a) neutral (favorite films), (b) personally threatening (personal fears), and (c) relationship threatening (possible reasons for separation from partner). Trustworthiness appraisal of the partner was assessed after each conversation by self-report. BPD patients did not differ from HC women on trustworthiness perception after the neutral conversation but reported diminished trustworthiness perception after both threatening situations compared to HCs. BPD patients’ trustworthiness perception was by trend decreased after the separation versus fear condition. The perceived tenderness in the relationship was a protective factor. The inability to maintain a stable image of a trustworthy partner during threatening situations might lead to difficulties in interpersonal relationships of patients with BPD. Although relationship threats possibly play a particular role in this context, trustworthiness perception decreases are not limited to this kind of threat. (PsycINFO Database Record (c) 2017 APA, all rights reserved)